Infiltration of Bapedi Culture by Early Western Christian Missionaries: Compliance and Cultural Resistance - Morakeng Edward Kenneth Lebaka (Current Progress in Arts and Social Studies Research Vol. 9, 2025)
It is deeply regretted that early Christian missionaries brought the good and bad to Africa. It is apparent that the coming into existence of the missionaries with the Bapedi people was conflict-ridden, and hence created a pull-and-push situation. This chapter highlights the history of Christianity in South Africa, particularly in the Bapedi society, but also scrutinizes the work of the Berlin (German) Missionary Society and other missionaries who infiltrated Bapedi culture, as well as the response by Bapedi people; resistance and compliance from 19 July 1860 – 8 July 2018. To achieve the objectives of this study, the following primary research questions were considered: a) How do people understand one another when they do not share a common cultural experience? and b) were the missionaries successful in accomplishing their mission by indoctrinating and detribalising Bapedi people to forget about their cultural heritage and identity? A contextual approach was employed, and data was collected through observations, interviews, and video recordings of rituals, and social and cultural ceremonies. Relevant sources to the context of this study in the form of published journal articles, book chapters, books and theses were also consulted to compare and complement data collected from the field research. It has emerged from this study that missionary activities in South Africa and elsewhere in the continent have generated a great deal of debate in the scholarly arena. During observations and interviews, it was also established that the missionaries were ignorant of the fact that Christianity in Bapedi society had to make provision for Bapedi traditional beliefs, customs and practices if it wanted to succeed. It was concluded that the missionaries did not take into consideration the traditional beliefs, customs and practices of the Bapedi people. Instead of adding towards Bapedi cultural practices, they applied the principle of elimination by substitution.